A COMPARISON OF MACERATION AND SOCKLETATION EXTRACTION METHODS ON FLAVONOID CONTENTS OF BELUNTAS LEAF EXTRACT - Handik Hendratama; Diana Novita Sari; Alifatun Nada; Aulia Firda Alfiana (Ekliptika, 2025)
This research aims to analyze the flavonoid compound of beluntas leaves (Pluchea indica L) using maceration and soxhletation extraction methods. Extraction uses 96% methanol solvent with a ratio of 1:10, 1:15, 1:20 w/v and with a soxhletation extraction time of 60 minutes, 120 minutes, 180 minutes at a temperature of 80oC, while the maceration time is 3 days at room temperature. Qualitative testing of flavonoid compounds uses the Shinoda test which is characterized by a change in the color of the sample to yellow or red-orange. The test results of all samples used showed the presence of flavonoid compounds which were characterized by changes in the color of the samples from yellow to red-orange. The research results showed that the best flavonoid content using the maceration extraction method was 51.52 mg QE/g at a ratio of 1:20 w/v, while the flavonoid content using the soxhletation extraction method was 53.96 mg QE/g at a ratio of 1:20 w/v.